Effect of Graft Choice on the Outcome of Revision Anterior Cruciate Ligament Reconstruction in the Multicenter ACL Revision Study (MARS) Cohort. (October 2014) - ,
Background: Most surgeons believe that graft choice for anterior cruciate ligament (ACL) reconstruction is an important factor related to outcome; however, graft choice for revision may be limited due to previously used grafts. Hypotheses: Autograft use would result in increased sports function, increased activity level, and decreased osteoarthritis symptoms (as measured by validated patient-reported outcome instruments). Autograft use would result in decreased graft failure and reoperation rate 2 years after revision ACL reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: Patients undergoing revision ACL reconstruction were identified and prospectively enrolled by 83 surgeons at 52 sites. Data collected included baseline demographics, surgical technique, pathologic abnormalities, and the results of a series of validated, patient-reported outcome instruments (International Knee Documentation Committee [IKDC], Knee injury and Osteoarthritis Outcome Score [KOOS], Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC], and Marx activity rating score). Patients were followed up at 2 years and asked to complete the identical set of outcome instruments. Incidences of additional surgery and reoperation due to graft failure were also recorded. Multivariate regression models were used to determine the predictors (risk factors) of IKDC, KOOS, WOMAC, Marx scores, graft rerupture, and reoperation rate at 2 years after revision surgery. Results: A total of 1205 patients (697 [58%] males) were enrolled. The median age was 26 years. In 88% of patients, this was their first revision, and 341 patients (28%) were undergoing revision by the surgeon who had performed the previous reconstruction. The median time since last ACL reconstruction was 3.4 years. Revision using an autograft was performed in 583 patients (48%), allograft was used in 590 (49%), and both types were used in 32 (3%). Questionnaire follow-up was obtained for 989 subjects (82%), while telephone follow-up was obtained for 1112 (92%). The IKDC, KOOS, and WOMAC scores (with the exception of the WOMAC stiffness subscale) all significantly improved at 2-year follow-up ( P < .001). In contrast, the 2-year Marx activity score demonstrated a significant decrease from the initial score at enrollment ( P < .001). Graft choice proved to be a significant predictor of 2-year IKDC scores ( P = .017). Specifically, the use of an autograft for revision reconstruction predicted improved score on the IKDC ( P = .045; odds ratio [OR] = 1.31; 95% CI, 1.01-1.70). The use of an autograft predicted an improved score on the KOOS sports and recreation subscale ( P = .037; OR = 1.33; 95% CI, 1.02-1.73). Use of an autograft also predicted improved scores on the KOOS quality of life subscale ( P = .031; OR = 1.33; 95% CI, 1.03-1.73). For the KOOS symptoms and KOOS activities of daily living subscales, graft choice did not predict outcome score. Graft choice was a significant predictor of 2-year Marx activity level scores ( P = .012). Graft rerupture was reported in 37 of 1112 patients (3.3%) by their 2-year follow-up: 24 allografts, 12 autografts, and 1 allograft and autograft. Use of an autograft for revision resulted in patients being 2.78 times less likely to sustain a subsequent graft rupture compared with allograft ( P = .047; 95% CI, 1.01-7.69). Conclusion: Improved sports function and patient-reported outcome measures are obtained when an autograft is used. Additionally, use of an autograft shows a decreased risk in graft rerupture at 2-year follow-up. No differences were noted in rerupture or patient-reported outcomes between soft tissue and bone–patellar tendon–bone grafts. Surgeon education regarding the findings of this study has the potential to improve the results of revision ACL reconstruction.